Selection of phytase-producing moulds - I.W.R Susana; B Tangenjaya; S Hastiono (Indonesian Center for Animal Research and Development (ICARD), 2000)
Organic phosphorous in the form of phytate salts are found in feed component originated from cereals which can not be digested by chicken unless after the addition of an enzyme, i.e. phytase. A research to investigate phytase-producing moulds had been carried out. A total of 60 isolates from various collection units and isolation from samples had been collected then screened in Czapek’s medium with Ca-phytate as the source of phosphorous. From mould growth measurements and clearing zones formation there were 4 mould isolates, i.e. Aspergillus ficuum NRRL 3135 and NRRL 320, Aspergillus niger M94/18/D2 (Balitvet isolate), and Aspergillus niger no. 58 (IPB isolate), which were further observed. Enzyme was produced from medium containing 8% of corn’s starch, 3% of glucose, 0.0005% of KCl and MgSO4.7H2O, 0.0002% of K2HPO4, and 0.00018% of FeSO4.7H2O. The enzyme activity, protein and biomass contents were observed at 16, 24, 32, 48 and 72 hours incubations for Aspergillus niger and at 1, 2, 3, 4 and 5 days incubations for Aspergillus ficuum. The highest protein content was found at 5 days incubation for Aspergillus ficuum NRRL 3135 and NRRL 320, (165 and 169 μg/ml respectively), while for Aspergillus niger (Balitvet and IPB isolates) at 16 hours incubation (102 and 112 μg/ml respectively). Meanwhile, the biomass contents were decreased in accordance with the duration of incubations. The maximum enzyme productions were reached at 24 hours incubation for Aspergillus niger and at 4 days incubation for Aspergillus ficuum. The highest phytase activities were reached at 2.808 U/ml for Aspergillus ficuum NRRL 3135, followed by 1.520 U/ml for Aspergillus ficuum NRRL 320. Aspergillus niger produced enzyme quicker than the other moulds, with lower activity level and decreases quicker at the following hours. Key words: Phytate, phytase, Aspergillus ficuum, Aspergillus niger